Concomitant Obesity and Metabolic Syndrome Add to the Atrial Arrhythmogenic Phenotype in Male Hypertensive Rats. Issue 9 (17th September 2017) - Hohl, Mathias; Lau, Dennis H.; Müller, Andreas; Elliott, Adrian D.; Linz, Benedikt; Mahajan, Rajiv; Hendriks, Jeroen M. L.; Böhm, Michael; Schotten, Ulrich; Sanders, Prashanthan; Linz, Dominik
Abstract : Background: Besides hypertension, obesity and the metabolic syndrome have recently emerged as risk factors for atrial fibrillation. This study sought to delineate the development of an arrhythmogenic substrate for atrial fibrillation in hypertension with and without concomitant obesity and metabolic syndrome. Methods and Results: We compared obese spontaneously hypertensive rats (SHR‐obese, n=7–10) with lean hypertensive controls (SHR‐lean, n=7–10) and normotensive rats (n=7–10). Left atrial emptying function (MRI) and electrophysiological parameters were characterized before the hearts were harvested for histological and biochemical analyses. At the age of 38 weeks, SHR‐obese, but not SHR‐lean, showed increased body weight and impaired glucose tolerance together with dyslipidemia compared with normotensive rats. Mean blood pressure was similarly increased in SHR‐lean and SHR‐obese when compared with normotensive rats (178±9 and 180±8 mm Hg [not significant] versus 118±5 mm Hg, P <0.01 for both), but left ventricular end‐diastolic pressure was more increased in SHR‐obese than in SHR‐lean. Impairment of left atrial emptying function, increase in total atrial activation time, and conduction heterogeneity, as well as prolongation of inducible atrial fibrillation durations, were more pronounced in SHR‐obese as compared with SHR‐lean. Histological and biochemical examinations revealed enhanced triglycerides and more pronounced fibrosis in the left atrium of SHR‐obese. Besides increased expression of profibrotic markers in SHR‐lean and SHR‐obese, the profibrotic extracellular matrix protein osteopontin was highly upregulated only in SHR‐obese. Conclusions: In addition to hypertension alone, concomitant obesity and metabolic syndrome add to the atrial arrhythmogenic phenotype by impaired left atrial emptying function, local conduction abnormalities, interstitial atrial fibrosis formation, and increased propensity for atrial fibrillation.